Governance Mining Licensing in Central Sulawesi Post Mining Law Reform and Law Job Creation - Meldi Amijaya; La Husen Zuada; Muhammad Ahsan Samad; Muhammad Akbar Hairi (Indonesian Journal of Social and Environmental Issues (IJSEI), 2022)
This article aims to explain the governance of mining permits after the reform of the mining law and the issuance of the law on job creation. The research design used descriptive qualitative. The results of the study found: First, the Ministry of energy and mineral resources is the leading sector in the management of the mining sector at the national level. Meanwhile, at the local government level, the provincial and district/city offices of energy and mineral resources are played. Second, in Central Sulawesi Province mining business permits are issued by the One Stop Service Investment Office. Before the omnibus law, there are at least five stages that are passed in the licensing process, namely the application for a mining business area permit, an application for an exploration mining business permit, an application for a principle permit for the use of national strategic area space, and an application for an Environmental Feasibility Decree and Environmental Permit, as well as an application for a production mining business permit. Third, the issuance of law number 11 of 2020 concerning job creation (omnibus law) reduces the authority of local governments in managing mining permits in Central Sulawesi. In addition, the omnibus law provides convenience in environmental management, where environmental permits are replaced with environmental approvals that are integrated with business permits.